2005
DOI: 10.1016/j.rmed.2004.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of asthma revisited upon the presence of atopy

Abstract: Immunological studies claimed that atopic and non-atopic asthma share more similarities than differences. However, these two phenotypes of asthma are considered to be distinguishable upon distinct clinical patterns, which were not systematically assessed before in a large population. We studied characteristics discriminating atopic from non-atopic asthma among 751 asthmatic patients and 80 factors were analysed in univariate and multivariate analysis. Age, age of onset of asthma, female/male ratio were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 27 publications
4
39
0
Order By: Relevance
“…These findings are strengthened by the inclusion of a large sample size, which allows for the detection of small differences between groups, as well as inclusion of a large population of women with allergic sensitization but not asthma. Furthermore, our results showing a Th2 bias in atopic subjects in response to antigen are consistent with previous findings in atopic asthmatics 7, 9, 26, 27. The strength of the associations in our study may be related to common exposure and sensitization to potent indoor allergens.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are strengthened by the inclusion of a large sample size, which allows for the detection of small differences between groups, as well as inclusion of a large population of women with allergic sensitization but not asthma. Furthermore, our results showing a Th2 bias in atopic subjects in response to antigen are consistent with previous findings in atopic asthmatics 7, 9, 26, 27. The strength of the associations in our study may be related to common exposure and sensitization to potent indoor allergens.…”
Section: Discussionsupporting
confidence: 93%
“…Experimental and clinical evidence indicates that nonatopic asthma is related with both T H 1 and T H 17 cell responses (Alcorn et al, 2010;Cho et al, 2005). Nonatopic asthma may thus share some properties with autoimmune disorders, such as T H 1 and T H 17 activity and higher disease risk in the female population (Nieves et al, 2005). Elevated levels of auto-antibodies, anti-nuclear antibodies and T lymphocytes activity have also been reported in nonatopic asthma (Rottem and Shoenfeld, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For the patient, however, it is not unimportant to distinguish between the two different phenotypes as Rackeman and later Romanet-Manent proposed [1,2]. Furthermore, Nieves et al [5] studied the characteristics discriminating allergic from non-allergic asthma and found that patients differed particularly in respect to sex and age at onset.…”
Section: Introductionmentioning
confidence: 99%